Persistent pathways after lung radiofrequency ablation as a risk factor of drain placement. (18th August 2017) - Lignieres, Marie; Roux, Nicolas; Giorgi, Roch; Gaubert, Jean-Yves; Chaumoitre, Kathia; Bartoli, Jean-Michel; Vidal, Vincent; Izaaryene, Jean
Abstract: Purpose: The risk factors of pneumothorax after lung radiofrequency (RF) ablation are long known. The objective was to demonstrate that the visualisation of an aeric RF path after the needle withdrawal was predictive of pneumothorax occurrence and chest tube placement. Materials and methods: A total of 70 patients were retrospectively included in this study. For each patient, we determined the pneumothorax risk factors (age, gender, previous surgery, emphysema, lesion size, distance between pleura and lesion), visualisation of a RF track, length and thickness, presence of pneumothorax, volume, chest tube placement, duration of drainage and hospital stay. Results: Among 70 patients included retrospectively, 26 needed a chest tube placement (37%). Considering the group with path visualisation (37 patients, group A) and the patients without path visualisation (group B), the 2 groups were comparable for pneumothorax risk factors. Considering the patients who needed a chest drain, the visualisation of the path was significatively more important (23 cases, 88.4%) ( p < 10 −3 ) than in the group without (8 patients, 31.8%). Multivariate analyses were significant in the three analyses after adjustments on the risk factors for the occurrence of pneumothorax. Incidence of drains was significantly more ( p  < 10 −3 ) important in group A (23 drainages 62%) than in group B (4 drainages or 12%). The length and thickness of the tracks were not predictable of drain placement. Conclusions: Besides the well-known risk factors of severe pneumothorax after lung RFA, the simple visualisation of an aeric path just after the RF needle withdrawal is significantly associated with chest tube placement and can be considered as a risk factor as itself.